AB0438 Vasculitis associated with large granular lymphocyte leukemia : presentation and treatment outcomes. (23rd January 2014) - Audemard, A.; Lamy, T.; Boutemy, J.; Lazaro, E.; Geffray, L.; schleinitz, N.; Verneuil, L.; Guillevin, L.; Bienvenu, B.
Abstract : Background: Large granular lymphocyte (LGL) leukemia represent ∼5–10% peripheral blood mononuclear cells. These include mainly cytotoxic T cells and natural killer (NK) cells. LGL disease has four forms: chronic or transient LGL lymphocytosis and aggressive or indolent LGL leukemia. Many autoimmune diseases have been reported associated with LGL diseases: e.g. rheumatoïd arthritis, immune thrombopenic purpura. The association between vasculitis and large granular lymphocyte (LGL) leukemia has rarely been reported or investigated. Objectives: Thus, we assessed the clinical and biological phenotypes of LGL leukemia associated with vasculitis. Methods: This retrospective study was conducted through the SNFMI ("Société Nationale Française de Médecine Interne") and the "Amicale des Jeunes Internistes". A total of 1552 internists were contacted by e-mail and asked to supply the medical characteristics of patients displaying LAV and LGL leukemia. Results: We studies a series of 11 patients displaying LGL leukemia associated with vasculitis (LAV). The mean age at diagnosis of LGL leukemia was 60.3 years; there were nine women, two men. The mean follow-up period was 45 months. The main LGL lineage was T-LGL (10 patients) and only one NK-LGL was identified. Clinical and biological features of T-LGL leukemia were compared with those from the 2009 French T-LGL registry. We did not find any relevant differences except that patients with LAV were predominantly female ( p <0.05). The most frequently observed vasculitis was cryoglobulinemia ( n =5). Three patients presented with single-organ vasculitis, two patients had ANCA-negative microscopic polyangiitis, and one patient had giant-cell arteritis. The main clinical features involved the skin, e.g., purpura (91%), arthralgia (37%), peripheral neuritis (27%), and renal glomerulonephritis (18%). The most frequent histologic finding was leucocytoclastic vasculitis (54%). The rate of complete remission was high: i.e., 80% with corticosteroid and immunosuppressive therapy. A minority of patients had a vasculitis relapse (27%). Three patients (27%) died: one related to LGL leukemia (acute infection) and two other deaths were related to vasculitis (both with heart failure). Conclusions: We conclude that vasculitis is overrepresented in the population of LGL patients, that LAV predominantly affects women, that vasculitis preferentially affects the small vessels, andthat LAV has high rate of complete response. Disclosure of Interest: None Declared